Rotator cuff impingement associated with Type III acromial morphology in a young athlete—a case for early imaging. Issue 1 (17th January 2017) - Inklebarger, James; Gyer, Giles; Parkunan, Anand; Galanis, Nikiforos; Michael, Jimmy
Abstract: Down-sloped or hooked acromion morphologies may cause bony encroachment on the soft tissues of the subacromial space, predisposing to shoulder impingement syndrome. Of the latter, a hooked or Type III acromion (T3A) has also been linked to rotator cuff (RC) pathology. However, as bony acromial impingement is typically thought to occur over the age of 40, its occurrence in younger shoulder athletes presenting with shoulder pain, impingement and RC pathology may be overlooked. This case serves to illustrate the occurrence of T3A in a younger shoulder athlete, and the importance of early imaging in achieving diagnostic accuracy. Appropriate surgical referrals are patients with subacromial impingement syndrome refractory to 3–6 months of appropriate conservative treatment. Surgery may be particularly beneficial in patients with a T3A.